155k views
0 votes
Please answer!!!!!!!!!!!

Please answer!!!!!!!!!!!-example-1
User Jhenninger
by
4.4k points

2 Answers

1 vote

Answer:

C.
f(a + 2) = (5 + a)/(a - 1)

Explanation:

Replace x with a + 2 and simplify the expression.


f(x) = (3 + x)/(x - 3)

Let x = a + 2


f(a + 2) = (3 + a + 2)/(a + 2 - 3)


f(a + 2) = (5 + a)/(a - 1)

User Wlk
by
5.1k points
5 votes

For this case we have a function of the form
y = f (x). Where:


f (x)=\frac {3 + x}{x-3}

We must find the value of the function when
x = a + 2

So, substituting the value of "x" we have:


f (a + 2) = \frac {3+ (a + 2)} {(a + 2) -3}


f (a + 2) = \frac {3 + a + 2} {a + 2-3}


f (a + 2)=\frac {5 + a} {a-1}\\

Answer:


f(a + 2) =\frac {5 + a} {a-1}

Option C

User VPP
by
5.1k points